ChemInform Abstract: Isoquinoline N‐Oxide Synthesis under Pd‐Catalyzed C—H Activation/Annulation Processes. Issue 15 (15th April 2014) - Li, Bingyao; Jiao, Pingxuan; Zhong, Hongban; Huang, Jianhui
Abstract The obtained isoquinoline N‐oxides can be readily reduced to the corresponding isoquinolines.